Evektivitas Implementasi Program Perumahan Bersubsidi bagi Masyarakat Berpenghasilan Rendah Kota Pekanbaru - M. Khairul Sandi; Nurlaila, Siti; Erinaldi, Erinaldi (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2025)
This study aims to analyze the effectiveness of the implementation of the subsidized housing program for low-income communities in Pekanbaru City. The background of this research stems from the high demand for decent housing among low-income groups and the government’s challenge in ensuring equitable access to affordable housing. The research method employed is descriptive qualitative with a policy study approach. Data were collected through in-depth interviews with officials from the Department of Public Housing and Settlement Areas, housing developers, banking institutions, and program beneficiaries. Field observations and documentation were also conducted to strengthen data validity. The results show that the implementation of the subsidized housing program in Pekanbaru City has been in line with national policies, yet its effectiveness remains suboptimal. This condition is influenced by insufficient policy dissemination, limited strategic land availability, inaccurate targeting of beneficiaries, and weak supervision mechanisms. On the other hand, supporting factors such as regulatory support, partnerships with the private sector, and accessible financing through subsidized home ownership loans have contributed to the program’s success. In conclusion, the effectiveness of program implementation can be improved through stronger inter-agency synergy, transparency of beneficiary data, and institutional capacity building so that the goal of equitable access to decent housing for low-income communities can be sustainably achieved.